WHY WE COULD NOT ERADICATE POLIO FROM PAKISTAN AND HOW CAN WE? - Shah, Syed Zawar; Saad, Muhammad; Khattak, Mohammad Hasan Rahman; Rizwan, Muhammad; Haidari, Asma; Idrees, Fatima (Journal of Ayub Medical College Abbottabad, 2016)
Polio is a major health problem and a deadly infectious disease in the developing countries. It is a viral illness caused by polio virus that can lead to paralysis, limb deformities, breathing problems or even death. Polio virus resides only in humans and passes on to the environment in the faeces of someone who is infected. Polio is still endemic in three countries, i.e., Pakistan, Nigeria and Afghanistan and is eradicated from the rest of the world. Pakistan is considered as the exporter of Wild Polio Virus (WPV) with highest number of polio outbreaks among endemic countries. With the start of World Polio Eradication Initiative in 1988, the number of polio cases has been reduced up to 99% worldwide until now. In 2015, Pakistan has shown a decrease of 70-75% in number of polio cases as compare to last year which is the result of good government’s initiatives. Militant organizations such as Tehreek-e-Taliban Pakistan, Al-Qaeda and Boko haram movement of northern Nigeria are a major hurdle in the eradication of polio from these countries. The misconception of people about polio vaccine, insecurity within the country and poor health system are the reasons of failure of polio eradication campaigns in these regions. Awareness campaigns about polio for locals and development of proper health system will help in the eradication of polio. Once polio is eradicated, about 40-50 billion dollars can be saved globally. With the strong commitment, seriousness and good initiatives, polio will be eradicated from Pakistan within two years more likely. Keywords: Poliomyelitis, prevalence, risk factors, strategies